2020
DOI: 10.36108/pajols/0202/40(0330)
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Metabolic Resistance in Pyrethroid Resistant Aedes aegypti Population from Lagos, Nigeria

Abstract: Background: Pyrethroid resistance in Aedes aegypti is of major concern to the control of several arboviral infections. The major mechanisms of Pyrethroid resistance in mosquitoes are target-site insensitivity and elevation in the activity of detoxification enzymes. In this study, we assessed the susceptibility status of Aedes aegypti population from Lagos to Pyrethroid and the impact of metabolic enzymes on resistance development. Methods: Larvae of Aedes aegypti were collected from differ ent habitats in Lago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Results from this study showed resistance to DDT and pyrethroid in the two study communities, similar to previous reports from Lagos State and other parts of southern Nigeria where resistance to DDT has been recorded in Aedes aegypti [6][7][8]. Resistance to bendiocarb was reported in Majidun community similar to previous report from Kwara State, north-central Nigeria [6] though a similar study in Lagos had reported susceptibility of Aedes aegypti in Lagos State to carbamates [7].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Results from this study showed resistance to DDT and pyrethroid in the two study communities, similar to previous reports from Lagos State and other parts of southern Nigeria where resistance to DDT has been recorded in Aedes aegypti [6][7][8]. Resistance to bendiocarb was reported in Majidun community similar to previous report from Kwara State, north-central Nigeria [6] though a similar study in Lagos had reported susceptibility of Aedes aegypti in Lagos State to carbamates [7].…”
Section: Discussionsupporting
confidence: 89%
“…However, resistance to insecticides is being reported in different mosquito species including Aedes aegypti in various parts of the world. In Nigeria, resistance to DDT, pyrethroids and carbamates have been reported in Aedes aegypti from different parts of the country [5][6][7][8]. Insecticide resistances in mosquitoes in mainly as a result of the activities of detoxifying enzymes and mutation of the target sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation